Professional WordPress : - Williams, Brad (John Wiley &​ Sons, Inc., 2013)
Offers an overview of the WordPress system and describes what happens when a WordPress-generated web page is displayed Demonstrates extending WordPress through plugins and customizing it via themes Combines a developer view of user experience and optimization with the deployment requirements for performance, security, and measurement Includes code downloads and code samples from the book's website